The effect of natural bioactive additives on the mechanical properties and optical and surface properties of conventional glass ionomer cement - Bastawy, Ahmed; Goda, Ahmed Ali; Elmanakhly, Ahmed Ramadan; Elsayed, Hosam Muhammed; Dewedar, Karim Sherif Adly; Sadek, Galal Eldeen Mosaad; Mekkey, Mahmoud Abd-Allah Mohammed (International journal of health sciences, 2021)
Objectives: To determine the effect of natural bioactive additives on the optical, mechanical, and surface characteristics of standard GIC. Materials and methods: The study included four tested groups: nano-hydroxyapatite (n-HA), Carumcarvi L. (Caraway), (Thymus vulgaris L) Thymol, and (Sesamum Indicum L) Sesame oils, and one control. The following parameters were evaluated: Diametral tensile, shear, Compressive, bond strength, solubility, Surface Roughness, and Color Stability. Results: Mechanical characteristics decreased significantly (p ≤0.05) in all adjusted cements compositions. Solubility and sorption were increased significantly (p ≤0.05) in all amended cement formulations except HA, which showed a non-significant rise in Water Sorption% and Solubility. Color difference mean values are clinically inappropriate (E > 3.3). The mean for 1 and 3% sesame oil-modified cement was lower (3.86 1.44 and 4.11 1.70, respectively). Surface roughness showed a significant difference between groups. Conclusion: Natural bioactive additions added to traditional glass ionomer cement did not improve its mechanical, optical, or surface qualities.